Regional private laws and codification in Europe - MacQueen, Hector L.; Vaquer i Aloy, Antoni; Espiau Espiau, Santiago (Cambridge University Press, 2003)
"Regions such as Scotland and Catalonia have their own legal systems: how will the process of 'Europeanisation' affect them? This volume examines the phenomenon of 'regional' private law in the European Union, considering jurisdictions and laws below those of the member states (such as Scotland and Catalonia) and drawing comparisons with other such jurisdictions elsewhere in the world, such as Louisiana and Quebec. The whole is considered in relation to the development of European private law, and the use of codification in the process. This volume will be of interest to academic lawyers worldwide, advanced law students and European policy makers"--Provided by publisher